Initial training and professional teaching practice: narrative of a Physical Education teacher (Research, Society and Development, 2022)
Studies on the professional trajectory and training of teachers are important for reflection on teacher training and professional development. The objective of this study is to unveil the relevant plots for the training of teachers in Physical Education and to interpret the initial trajectory of teacher training. This study is characterised as a qualitative approach, where the narratives of a Physical Education teacher were collected through the interview technique, from which an analysis was carried out that dialogued with the thinking of other authors. The results indicate that knowing the life story of a teacher, focussing on the constitution of their initial training, gives us the possibilities to understand that such training is part of a historical process.